Minerals and fatty acids profile of armored catfish Pterygoplichthys pardalis from Ciliwung River, Indonesia - FAHMA WIJAYANTI; ADE LISDANIYAH; MAULIDATUL HASANAH; DEWI ELFIDASARI (Smujo International, 2023)
Abstract. Wijayanti F, Lisdaniyah A, Hasanah M, Elfidasari D. 2023. Minerals and fatty acids profile of armored catfish Pterygoplichthys pardalis from Ciliwung River, Indonesia. Nusantara Bioscience 15: 58-67. Fish is an important food source in human consumption due to its minerals and fatty acids needed for various body functions. One fish widely eaten by the people around the Ciliwung River, Indonesia is the armored catfish, Pterygoplichthys pardalis (Castelnau 1855). It has great economic value and is easily obtained by the residents along this river. Due to its high protein content, P. pardalis is a potential source of animal protein for humans. The unavailability of information detailing the minerals content and fatty acids in P. pardalis from the Ciliwung River makes it necessary to conduct this research to analyze the fish's minerals content and fatty acid profile. Analyses of minerals, fatty acid contents, and fatty acid profiles were conducted using Atomic Absorption Spectrophotometry (AAS), socletation, and Gas Chromatography-Mass Spectrophotometer (GC-MS) methods, respectively. The mineral content of P. pardalis from the highest order was calcium, phosphorus, potassium, magnesium, sodium, iron, and zinc. Based on P. pardalis body size, large fish had the highest calcium concentration content, and the lowest calcium content was found in the medium fish. The fat content in this fish was very low (<1%), and the content of Saturated Fatty Acids (SFA) was greater than unsaturated ones. Furthermore, palmitate acid was the dominant fatty acid in the fish, while the biggest ratio of omega-6: omega-3 is fatty acids.